Government policies and entrepreneurship phases in emerging economies: Nigeria and South Africa - Folashade O. Akinyemi; Oluwabunmi O. Adejumo (Journal of Global Entrepreneurship Research, 2018)
This paper introduces entrepreneurship phases in studying the impact of some government policies on entrepreneurial activities. Entrepreneurship and small business development are the heart of many countries economy, and countries that give entrepreneurship special attention stand better chances of improved economy and industrialization. World over, it is well known that government policies often affect entrepreneurial activities directly and indirectly. But the question is do these policies have equal impact in every entrepreneurship phase. Hence, this study seeks to examine some policy factors that enhance entrepreneurial activities in two of African's emerging economies. And precisely, to identify the most favorable government policy in each entrepreneurship phase. This study was conducted in the economic hub of two African emerging economies (Nigeria and South Africa), where most entrepreneurial activities take place. A total of 1200 questionnaires (650 in Lagos, Nigeria and 550 in Johannesburg, South Africa) were administered. The analysis was in two stages; stage one involved descriptive statistics while stage two involved inferential statistics. Also, Principal Component Analysis (PCA) was used to identify the most favorable government policy in each entrepreneurship phase. The results show that some variations exist in the policy implementation approaches of both economies. The efficacies and shortcomings associated with the policies impacted entrepreneurial activities. The findings show that the impact of government policies on entrepreneurship phases differ in both countries. The study concluded that some policies are more favorable than others in some phases. Hence, makes a clarion call for more studies on government policies across entrepreneurship phases.
Keywords: 650; Government policies; Entrepreneurship phases; Emerging economies